CLOUD-BASED ERP SYSTEM ADOPTION IN IRAQI SMES: A QUALITATIVE APPROACH TO IDENTIFY AND EVALUATE THE AFFECTING FACTORS - MOHAMMED, GHAITH JAAFAR; Mohd Aboobaider, Burhanuddin; Alyousif, Shahad; Alkhayyat, Ahmed; Hasan Ali, Mohammed; Malik, Rami Qays; Jaber, Mustafa Musa (Department of "Computer Integrated Manufacturing System", 2022)
Cloud Enterprise Resource Planning (ERP) solutions offer broad advantages to small and medium-sized businesses (SMEs). Yet, the motivation of SMEs’ decision maker to adopt this system is limited. Our research sought to investigate the identified logistic determents to cloud ERP system adoption experienced by SMEs’ decision maker. To meet this objective, an exploratory research approach including semi-structured interviews with SMEs’ decision maker was adopted. Video call interviews were used to conduct semi-structured interviews. Interview methodology was utilised to obtain information, views, and issues experienced by SMEs’ decision maker on their approach to adopting cloud ERP systems. This study includes eighteen (18) SMEs' decision makers who are directly involved and responsible for technology acquisition and policy decisions for their SMEs in the Republic of Iraq. The current study uses a thematic analysis to identify themes from the exploratory method. Ten (10) themes found having positive perception to adopt cloud ERP among SMEs. Also, the interviews also highlighted new themes. This exploratory study addresses a gap in the body of knowledge on cloud ERP adoption and offers guidance for future research by academics and industry professionals